Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/pai.13403
|View full text |Cite
|
Sign up to set email alerts
|

Blood eosinophil count as predictor of asthma exacerbation. A meta‐analysis

Abstract: Background: Evidence about the association of high blood eosinophil count with asthma exacerbation is inconsistent and unclear. The objective of this meta-analysis was to determine whether elevated blood eosinophil count predicts asthma exacerbation. Methods: We searched MEDLINE, EMBASE, and additional databases, without any language restriction. We also checked the reference lists of the included studies and of relevant systematic reviews. The main outcome was the occurrence of asthma exacerbation. We calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 53 publications
(152 reference statements)
0
20
0
Order By: Relevance
“…Peripheral blood eosinophil counts as high as 400 cells/mm 3 have been linked to increased asthma exacerbations; however, patients with adult-onset asthma who have blood eosinophil counts ≥ 300 cells/mm 3 present with a distinct phenotype of severe asthma that includes frequent exacerbations and a poor prognosis [ 16 ]. Blood eosinophil counts ≥ 200 cells/mm 3 have been associated with asthma exacerbation, including asthma-related outpatient visits and emergency department visits [ 17 ]. Studies of anti-eosinophilic therapies indicate that patients with blood eosinophil counts ≥ 300 cells/mm 3 can benefit from targeted treatment [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral blood eosinophil counts as high as 400 cells/mm 3 have been linked to increased asthma exacerbations; however, patients with adult-onset asthma who have blood eosinophil counts ≥ 300 cells/mm 3 present with a distinct phenotype of severe asthma that includes frequent exacerbations and a poor prognosis [ 16 ]. Blood eosinophil counts ≥ 200 cells/mm 3 have been associated with asthma exacerbation, including asthma-related outpatient visits and emergency department visits [ 17 ]. Studies of anti-eosinophilic therapies indicate that patients with blood eosinophil counts ≥ 300 cells/mm 3 can benefit from targeted treatment [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, eosinophilia is considered a prognostic marker and can be associated with frequent asthma exacerbations [ 21 , 60 ]. High eosinophil counts in the blood can be linked to an increase odds of asthma exacerbation [ 23 ]. Recent studies reported that patients with a blood eosinophil count greater than 400 cells/μl experienced severe asthma exacerbation, acute respiratory conditions, and a risk for airflow obstruction among asthma patients [ 54 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophilia can be related to the severity of the disease [ 20 , 21 ]. It is known to be an independent risk factor for asthma exacerbations, emergency department visits, and hospitalization due to asthma [ 22 , 23 ]. In addition, eosinophilia is related to an increased risk of moderate and severe asthma exacerbations [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, regarding the fact that serum IgE level increases in asthmatic patients, the results of several studies as well as the current one have corroborated it. [14][15][16][17][20][21][22] Davila et al conducted a multicenter, retrospective, observational study including 383 patients with allergic asthma adult patients. They aimed to evaluate the association between serum total IgE levels and disease severity in adult patients with persistent allergic asthma and to explore the main predictors of IgE levels.…”
Section: Dovepressmentioning
confidence: 99%